1976
DOI: 10.1148/121.2.281
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Manifestations of Pulmonary Histoplasmosis: A 10-Year Review

Abstract: Of 269 patients with histoplasmosis, 259 had radiographic manifestations of the disease. Of these, 217 showed multiple or solitary nodules, 28 infiltrates, 25 adenopathy, 5 fibrosing mediastinitis, 5 cavitation (3 infiltrates, 2 nodules), and 1 pleural effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Cavities were most commonly located in the upper lobes and accompanied by infiltrates and pleural thickening. Another review of cases of pulmonary histoplasmosis presenting to the Mayo Clinic in Rochester, Minnesota, from 1964 to 1974 reported that only 5/269 (1.8%) patients had pulmonary cavitation (72). The chronicity of infection in the Mayo Clinic series was not reported.…”
Section: Histoplasmosis the Dimorphic Fungusmentioning
confidence: 99%
“…Cavities were most commonly located in the upper lobes and accompanied by infiltrates and pleural thickening. Another review of cases of pulmonary histoplasmosis presenting to the Mayo Clinic in Rochester, Minnesota, from 1964 to 1974 reported that only 5/269 (1.8%) patients had pulmonary cavitation (72). The chronicity of infection in the Mayo Clinic series was not reported.…”
Section: Histoplasmosis the Dimorphic Fungusmentioning
confidence: 99%
“…Chest X-ray usually reveals diffuse pulmonary interstitial infiltrates. 35 The fungi may be associated with granulomatous reaction and the necrotic lesions may calcify.…”
Section: Disseminated Diseasementioning
confidence: 99%
“…Acute symptoms (fever, headache, cough and chest pain) can be present and commonly are mistaken for a flu-like illness [48] . The typical radiographic pattern is that of an acute bronchopneumonia.…”
Section: Symptomatic Acute Histoplasmosismentioning
confidence: 99%
“…A focal or diffuse reticulonodular pattern, linear and irregular opacities that progress rapidly to segmental, lobar, or diffuse areas of consolidation, make up the second pattern. Pleural effusions are infrequent, and lymphadenopathy is rarely seen in disseminated disease [47,48] .…”
Section: Disseminated Histoplasmosismentioning
confidence: 99%